A Data-Driven Approach for Enhancing Customer Loyalty through Strategic Business Innovations and Technology Integration - Venkataramana Karri; Polamarasetty Nooka Appa Rao; Gopal Krishna Sanapala; V Vijaya Kumar; Venkata Naga Siva Kumar Challa (Ianna Journal of Interdisciplinary Studies)
Background: Customer trust and loyalty are critical in today’s competitive business environment. Integrating technology, sustainability, and omnichannel approaches has been recognised as a key factor in enhancing customer experience. However, most existing qualitative studies lack statistical validation and a comprehensive view of how business strategies influence customer engagement.